Prevalence of Hypertension in Akwa Ibom State, South-South Nigeria: Rural versus Urban Communities Study - Effiong Ekong Akpan; Udeme E. Ekrikpo; Aniema I. A. Udo; Bassey Edet Bassey (International Journal of Hypertension)
Recent studies have shown an increasing trend in the prevalence of hypertension in rural communities compared to that of the urban communities. This study was therefore carried out to determine the prevalence of hypertension and its predictors (if any) in both urban and rural communities of Akwa Ibom State of Nigeria. Subjects and Method. This was a cross-sectional study of urban and rural communities of Akwa Ibom State for the prevalence of hypertension and its predictors. Two urban cities and two rural communities were randomly selected from the three senatorial districts of the state. Hypertension was defined based on the Seventh Report of the Joint National Committee on the Prevention, Detection, Evaluation, and Treatment of Hypertension. Results. Nine hundred and seventy-eight (978) participants were recruited from rural areas and five hundred and ninety (590) from urban centers. The rural populace had higher systolic, diastolic, and mean arterial blood pressure than the urban populace (P<0.001, < 0.002, < 0.001, resp.). The prevalence of hypertension was significantly higher in the rural populace than in the urban populace [44.3% (95% CI 41.1–47.4%) versus 28.6% (95% CI 24.9–32.3%)]. Age, BMI, and proteinuria were independent predictors of hypertension occurrence. Conclusion. There is an epidemiologic change in the prevalence of hypertension in the rural communities of Nigeria.